Machine Learning Approach for Prediction of MHC Binding Peptides - Dr. Virendra S. Gomase, Sonu Mishra, Dr. Chetan Kumar Sharma (International Journal of Advanced Science and Technology, 2020)
NADH dehydrogenase subunit 4L is a subunit of NADH dehydrogenase (ubiquinone). This protein has clinical significant role with BMI (Body Mass Index. Body mass index) in adults and entailed in metabolic disorder inclusive of obesity, hypertension and diabete. In this present study we predicted the MHC binding peptide through machine learning approach. In this investigation, we used ANNPred (artificial neural networks Prediction: A online web based tool), MHC2Pred which is an SVM (support vector machines) based approach for the prediction of the MHC binder peptides of MHC class I and class II .We also predicted the B cell epitopes from the antigen sequence or protein sequence through artificial neural network which is a machine based technique that is ABCpred server (Artificial neural network based B-cell epitope prediction server). There are the future chances that the antigenic peptide of NADH dehydrogenase subunit 4L (mitochondrion) protein can act as a significant role and shows the prospects of inventing a new subunit vaccines from this protein.